(untitled) (Journal of actual problems of jurisprudence, 2019)
On scientific work, that was named, to perfect questions of anticipating voracity and her a right protects efficiency application in experience office workers of organs examined theoretical approach lines increase. And also fight and measures of anticipating to renew voracity, according to conclusions in character of suggestion, examined questions introduction dowry and in laws. Key words: Corruption, corruption crimes, post crimes, counteractions of corruption, fi ght against a corruption.